Optimizing Bus Routes in Detroit, Michigan: an Analysis of Relevant Destinations, Origins and the Routes Connecting Them - Hrubecky, Jacob; Sherer, Will; Franczyk, Xavier (My University, 2018)
Due to a high population of residents without personal cars and the limited extent of bus routes in Detroit, Michigan, the city could benefit significantly from redesigned bus routes. We are going to perform a route and site suitability analysis in order to establish new bus routes in Detroit. We want to create a data layer representing new bus routes that form a more extensive and efficient network of public transportation services than currently exists. The design of new bus routes for Detroit will be guided by an emphasis on the importance of access to critical resources, like business districts, food, healthcare, and schools, for people of all socioeconomic statuses.
Includes Figures, Maps, Charts and Bibliography. Related files also included.
Keywords: Detroit; Bus routes